Exit wounds - Modan, Rutu 1966- (Drawn & Quarterly, 2007)
Set in modern-day Tel Aviv, a young man, Koby Franco, receives an urgent phone call from a female soldier. Learning that his estranged father may have been a victim of a suicide bombing in Hadera, Koby reluctantly joins the soldier in searching for clues. His death would certainly explain his empty apartment and disconnected phone line. As Koby tries to unravel the mystery of his father's death, he finds himself piecing together not only the last few months of his father's life but his entire identity